Sports Bras Improve Chest Keloids but Outcomes Are Dependent on Breast Size: A Retrospective Analysis - Zhu, Yanting; Zhang, Qiguo; Gong, Ting; Zhang, Peng; Cheng, Bo; Liu, Jian; Ji, Chao (Frontiers in Oncology, 2022)
Our study is a retrospective medical record review performed on 95 female keloid patients with the standard therapy combining complete surgical excision with superficial X-ray radiation. We aimed to analyze the relationship between breast size and treatment outcomes as well as the benefits of sports bras in the postoperative management of keloids. The results showed that the keloid score of no sports bra group was significantly worse than the score of sports bra group at 1-year follow-up. In addition, the large breast size group showed more significant improvement of keloid score when wearing sports bras. Our study highlights that continuous wearing a sports bra effectively reduces the skin tension of the postoperative incision and promotes recovery, especially for patients with large breast size.